Antibacterial and Cytotoxic Actions of Chloroform Crude Extract of Leptadenia hastata (Pers) Decnee - Umaru, Isaac John; Fasihuddin Badruddin, Ahmad; Zaini, Assim; Hauwa, Aduwamai Umaru (OMICS International, 2018)
hloroform extract of Leaves of Leptadenia hastata. The Bacterial effects was tested against 4 bacteria namely Salmonella typhi, Escherichia coli, Staphylococcus aureus, and Klebsielia pneumonia. Methods: The bacterial effect of the plant Leptadenia hastata was evaluated for potential antimicrobial properties in vitro by agar well diffusion method with four standard bacterial strains. Artemia salina; a brine shrimp species; was used to asses’ cytotoxic activity of the plant extract. Result: Among the subjected four bacteria; in case of Staphylococcus aureus, E. coli and Salmonella typhi; their zone of inhibition was higher (1.13 ± 0.15, 1.23 ± 0.12 and 1.03 ± 0.06) at 1000 ppm concentration. Whereas in the case of Klebsielia pneumonia, the zone of inhibition was higher (1.13 ± 0.06) at 500 ppm. The extract exhibited, effectiveness against the four species of bacteria was significant. Cytotoxicity property which was reflected in LC50 value and was found to be dose dependent manner Conclusion: The present results showed potential of the medicinal plant used by traditional herbal medical practitioners as natural anti-bacteria and can effectively be used for its significant action. It is also an effective cytotoxic agent and thus justify its use among herbal medical practitioners.